Wika at Lipunang Pilipino Sa Panahon ng Pandemiya At Krisis: Mga Namumuong Polisiya ng Ikalawang Administrasyong ng Ikalawang Administrasyon Marcos - San Juan, David Michael M. (Likhaan: The Journal of Contemporary Philippine Literature; Vol 16 No 2 (2022): Dx Machina: Philippine Literature in the Time of COVID-19, 2024)
This essay is aimed at swiftly scrutinizing the incipient policies of the second Marcos administration with regard to language issues and other related matters in the midst of the pandemic and crisis which the people continue to endure. The essay also includes a discussion on the meaningful proposals that serve as “light in the darkness” for those who are still optimistic in transforming the reality (just like the hope expressed in Rivermaya’s song which became popular again in the presidential campaign of former Vice President Leni Robredo), and evidence “that not everyone slept in the long night of our forefathers” (in a scene involving Pilosopong Tasio/Tasio the Philosopher in Jose Rizal’s novel Noli Me Tangere) for those who are already pessimistic, given the current situation